Parasitic phases at the origin of magnetic moment in BiFeO3 thin films grown by low deposition rate RF sputtering - Mori, Thiago J. A.; Mouls, Caroline L.; Morgado, Felipe F. [UNESP]; Schio, Pedro; Cezar, Júlio C. (AIP Publishing, 2017)
A series of epitaxial BiFeO3 thin films has been grown under high partial pressure in a pure O2 atmosphere, which leads to a low deposition rate. The samples grown under these conditions have presented an evolution of the quality of the epitaxy as the deposition temperature increases, however, spurious β-Bi2O3 and supertetragonal BiFeO3 phases are present in the films grown at higher temperatures. The presence of γ-Fe2O3 is reported in one growing condition, and has been attributed to the origin of hysteretic ferromagnetic behavior. A second kind of magnetism, with higher magnetic moment and anhysteretic behaviour, is attributed to the presence of mixed phases of BiFeO3.